Avoiding High Pressure Abdominal Closure of Congenital Abdominal Wall Defects-One Step Further to Improve Outcomes - Raluca-Alina Mocanu; Cătălin Cîrstoveanu; Mihaela Bizubac; Ionuț Fernando Secheli; Nicolae Sebastian Ionescu (MDPI AG, 2023)
The main goal of surgical treatment for gastroschisis and omphalocele is the reduction of viscera in the abdominal cavity and closure of the abdomen, but the challenge is to succeed without the detrimental effects of increased intraabdominal pressure. In this regard, we performed a retrospective study for all patients admitted for gastroschisis and omphalocele to the Neonatal Intensive Care Unit of 'Marie Sklodowska Curie' Emergency Clinical Hospital for Children, from January 2011 until June 2021. Our aim was to highlight the presence of postoperative abdominal compartment syndrome. We observed that six out of forty-seven patients developed clinical signs of abdominal compartment syndrome, five associated with primary closure and one with staged closure with a polyvinyl chloride patch. Following the results, we decided to implement the trans-bladder measurement of intraabdominal pressure to avoid closing the abdomen at pressures higher than 10 mmHg in order to prevent the development of abdominal compartment syndrome. We consider that there is still place for the improvement of congenital abdominal wall defects management and that the measurement of intraabdominal pressure might help us reach our goal.